Varietal Susceptibility of Yellow Onions to Blanching and Its Impact on Probiotic Fermentation - Katarzyna Grzelak-Błaszczyk; Robert Klewicki; Sylwia Ścieszka; Lidia Piekarska-Radzik; Michał Sójka; Michalina Jaszczak; Elżbieta Klewicka; Bartosz Fotschki; Jerzy Juśkiewicz (Molecules, 2025)
The purpose of this study was to determine the impact of blanching various onion (Allium cepa L.) varieties on the process of lactic fermentation by probiotic strain Levilactobacillus brevis ŁOCK 0944. The materials for the research were twelve varieties of yellow onion: Venecia, Moondance, Sedona, Alonso, Hysky, Centro, Dormo, Hypark, Hybelle, Armstrong, EXP 2236, and Hysinger. We also studied the resulting changes in bioactive compound content. Acidic bacterial metabolites, the lactic acid bacteria count, and the polyphenol and carbohydrate contents were assessed in both raw onions and onions blanched at 60 °C, before and after fermentation. Onion varieties that showed morphological changes after blanching (Hysky, Centro, Dormo) demonstrated better growth of L. brevis and higher lactic acid production. Blanching loosened the tissue structure, reducing the carbohydrate content in the blanched and fermented onions, particularly Alonso, Centro, Dormo, and Hypark varieties. Although the combined process reduced the polyphenol content, four varieties showed no statistically significant differences, indicating variety-specific responses. The varying susceptibility of onion varieties to thermal treatment highlights the importance of selecting the appropriate variety for further processing.